2013
DOI: 10.1007/s11745-013-3778-2
|View full text |Cite
|
Sign up to set email alerts
|

Sesamol Treatment Reduces Plasma Cholesterol and Triacylglycerol Levels in Mouse Models of Acute and Chronic Hyperlipidemia

Abstract: The active constituents of Sesamum indicum, sesamin and sesamolin, have already been explored for hypolipidemic action. In this study we have explored the anti-dyslipidemic activity of another active component and metabolite of sesamolin (sesamol), by using acute models of hyperlipidemia viz., a fat tolerance test, a tyloxapol-induced hyperlipidemia model and a chronic model of hyperlipidemia viz., a high-fat diet-induced hyperlipidemia model in Swiss albino mice. Sesamol (100 and 200 mg/kg) significantly (P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…Most noteably, evidence suggests that sesamol has cardioprotective benefits by regulating vascular function and influencing circulating lipids by modulating liver function. One clinical study showed that sesame seed oil can control increased blood pressure, hyperlipidemia and lipid peroxidation (by increasing enzymatic and non-enzymatic antioxidants (41) and similar findings have been highlighted in preclinical studies (42, 43, 44). Sesamol treatment reduced plasma cholesterol and triglycerides in acute and chronic hyperlipidemia, improved vascular function (42) and can up regulate protective vascular enzymes such as peroxisome proliferator-activated receptors (43, 44) in the liver.…”
Section: Sesamolsupporting
confidence: 54%
“…Most noteably, evidence suggests that sesamol has cardioprotective benefits by regulating vascular function and influencing circulating lipids by modulating liver function. One clinical study showed that sesame seed oil can control increased blood pressure, hyperlipidemia and lipid peroxidation (by increasing enzymatic and non-enzymatic antioxidants (41) and similar findings have been highlighted in preclinical studies (42, 43, 44). Sesamol treatment reduced plasma cholesterol and triglycerides in acute and chronic hyperlipidemia, improved vascular function (42) and can up regulate protective vascular enzymes such as peroxisome proliferator-activated receptors (43, 44) in the liver.…”
Section: Sesamolsupporting
confidence: 54%
“…1) has a wide range of biological actions, including: anti-mutagenesis [1]; antioxidant [2]; suppression of neuro-inflammation [3]; inhibition of atherosclerosis progression [4]; inhibition of NF-B in platelet aggregation [5,6]; and, reduction of plasma cholesterol and triacylglycerol levels [7].…”
Section: Introductionmentioning
confidence: 99%
“…Sesamun indicum is an ancient crop with high oil content in the seeds [22]. Sesame oil is a common edible oil, high in vitamins, minerals, phytosterols, and polyunsaturated fatty acids [17].…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that sesamol could induce apoptosis in HepG2 cells [21]. Sesamol also reduced cholesterol and triacylglycerol levels in hyperlipidemic mice [22]. In addition, sesamol was reported to have an anti-inflammatory effect in a rat inflammatory lung model and an antioxidant effect in a rat acute pancreatitis model [23].…”
Section: Introductionmentioning
confidence: 99%